2012
DOI: 10.1080/00288233.2011.644628
|View full text |Cite
|
Sign up to set email alerts
|

Pasture dry matter responses to the use of a nitrification inhibitor: a national series of New Zealand farm trials

Abstract: The use of nitrification inhibitors has become increasingly common on dairy farms in NZ since 2004, ostensibly to reduce nitrogen (N) loss from nitrate leaching and nitrous oxide emissions. A potential benefit of this reduction in N loss, however, is an increase in dry matter (DM) production. Pasture response data were collated from a national series of farm trials conducted in 132 paddocks on 37 farms in the North Island (NI) and South Island (SI) of New Zealand where paddocks were randomly split into two hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 10 publications
(13 reference statements)
1
16
0
Order By: Relevance
“…The effects of DCD on pasture production, as measured in the large-plot trials discussed above, are not as large as those reported by Carey et al (2012). Furthermore, these results do not require the explanation offered by those authors of a 'farmÁsystem effect'.…”
Section: Letter To the Editormentioning
confidence: 55%
See 3 more Smart Citations
“…The effects of DCD on pasture production, as measured in the large-plot trials discussed above, are not as large as those reported by Carey et al (2012). Furthermore, these results do not require the explanation offered by those authors of a 'farmÁsystem effect'.…”
Section: Letter To the Editormentioning
confidence: 55%
“…The response to eco-n TM relative to the control was 3.1% (NS) when pasture production was assessed using the traditional cage/mowing technique and 15.3% when pasture production was assessed using a plate meter. Thus, it appears that pasture plate meters introduce a bias sufficient to explain the difference between the large average response of 19% reported by Carey et al (2012) and the balance of the evidence summarised above.…”
Section: Letter To the Editormentioning
confidence: 94%
See 2 more Smart Citations
“…This indicates that the dominant loss pathways will differ between systems, years and seasons. A synopsis of pasture trials conducted on 132 paddocks in 37 farms across New Zealand found overall biomass benefits from the use of a nitrification inhibitor (DCD) (19% increase), with variation around this dependent upon the region (Carey et al 2012). The authors of the New Zealand study point out that this benefit is greater than reported on previous individual small plot studies (Carey et al 2012).…”
Section: Biomassmentioning
confidence: 99%